Skip to content

Skew-Symmetric Matirx

24/03/2011

Let A\in R^n, A is a skew-symmetric matrix if and only if x^TAx=0, \forall x\in R^n

Proof:

Necessity: if A is a skew-symmetric matrix, then A^T=-A. Hence (x^TAx)^T=x^TA^Tx=-x^TAx. Note (x^TAx)^T=x^TAx, hence x^TAx=-x^TAx=0.

Sufficiency: if x^TAx=0, \forall x\in R^n, then x^T(A+A^T)x=0. I think we need the lemma that if A is a symmetric matrix, then x^TAx=0, \forall x\in R^n if and only if A=0. Since A+A^T is a symmetric matrix, from x^T(A+A^T)x=0 we know A+A^T=0. Hence A is skew-symmetric.

QED

EDIT: The proof of sufficiency above is not correct. See here for a correct proof.

The below is a simpler proof.

Since x^TAx=0, \forall x,

e_i^TAe_i=0, so A_{ii}=0;

(e_i+e_j)^TA(e_i+e_j)=0, so A_{ij}+A_{ji}=0.

Hence A=-A^T.

Advertisements
No comments yet

Leave a Reply

Please log in using one of these methods to post your comment:

WordPress.com Logo

You are commenting using your WordPress.com account. Log Out / Change )

Twitter picture

You are commenting using your Twitter account. Log Out / Change )

Facebook photo

You are commenting using your Facebook account. Log Out / Change )

Google+ photo

You are commenting using your Google+ account. Log Out / Change )

Connecting to %s

%d bloggers like this: